A Theological-Ethical Study of Church Against Corruption - Yosefo Gule (International Journal Labs, 2022)
In this paper, the author conducted a theological-ethical study of the Church's role against corruption. The research method in this article uses a descriptive qualitative study method with a library research approach. The practice of corruption is an act that is contrary to the will and character of God. If the behavior of corruption is not resisted, then corruption seems to be a natural act and is no longer seen as an act of crime and sin. The Church, as a religious institution, is also responsible for fighting corruption in Indonesia and providing a formula that can support minimizing corruption that occurs in the life of the nation, society, and Church. The Church plays an essential role in fighting corruption as an agent of change to raise awareness in the community that corruption is a sin and an act against God's will. The role of the Church is significant in fighting corruption by strengthening the sanction mechanism in church administration, supporting anti-corruption programs in the Church, and minimizing the inclusion of a hedonic lifestyle in the lives of church members. It is hoped that through internal control measures in the Church, corruption can be minimized amid the Church and public life in general.